Rediscovery of the Endangered Khasi Hills Rock Toad, Bufoides meghalayana in Meghalaya, Northeastern India - Das, Indraneil; Rangad, Duwaki; Lyngdoh, Ronald K.; Deuti, Kaushik; Hooroo, Rupa Nyalla K.
Bufoides meghalayana, the Khasi Hills Rock Toad, is an Endangered species of tropical bufonid (Stuart et al., 2008), restricted to the Mawblang Plateau, ca. 5 km south of Cherrapunjee, East Khasi Hills, Meghalaya State, north-eastern India. Since its discovery by Yazdani and Chanda (1971: as Ansonia meghalayana), and reallocation to the monotypic genus Bufoides by Pillai and Yazdani (1973), it has been cited only in regional reviews (e.g., Chanda 1994; 2002) and in checklists (Frost 1985; Dutta 1997).